MENGEMBANGKAN ETIKA BERMEDIA SOSIAL PESERTA DIDIK MELALUI PENGUATAN MATERI AJAR PADA MATA PELAJARAN PAI - Sayid Ahmad Ramadhan; Zainap Hartati; Muslimah Muslimah; Noor Fahmi (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study is to discuss the strengthening of PAI teaching materials in developing students' social media ethics in the realm of moral ethics and social ethics. Library research becomes a type of research. The results show that the subject of Islamic Religious Education (PAI) with a series of subjects or content of teaching materials, can be a solution to fortify students and be able to develop social media ethics in the realm of moral ethics and social ethics for each. The efforts or ways that can be done are through strengthening PAI teaching materials with the following steps: first, integrating PAI teaching materials with phenomena that occur on social media. second, the development of PAI materials and curriculum. third, strengthening with orientation in the form of character education and fourth, evaluations that are carried out regularly. So that the final results obtained will make students better understand how to interact with fellow social media users while still applying the content of the material.